Strap: a versatile transcription co-factor. - Xu, D; La Thangue, N (2008)
The Stress-responsive activator of p300 (Strap) is a transcription co-factor that has an important role in the control of DNA damage response through its ability to regulate p53 activity. Recent studies have however suggested that Strap takes on a wider role in regulating the cellular response to stress. Thus, Strap is now known to be inducible by heat shock and stimulate the transcription of heat-shock genes. A chromatin-associated complex involving heat-shock factor 1 (HSF1), Strap and the p300 co-activator assembles on the HSP70 gene promoter, and Strap augments HSF1 binding and chromatin acetylation in HSP genes, most probably through recruiting p300 acetyltransferase. Cells depleted of Strap do not survive under heat-shock conditions. It appears therefore that Strap is an essential co-factor that acts at the level of chromatin control to regulate heat-shock-responsive transcription. These recent studies underscore the central role taken on by transcription co-factors in integrating and co-ordinating different cellular stress response pathways.